Robot Online Task and Trajectory Planning using Mixed-Integer Model Predictive Control - Tika, Argtim; Gashi, Fatos; Bajcinca, Naim (2022 European Control Conference (ECC), 2022)
A monolithic integration of the robot online task allocation and trajectory planning within the framework of a hybrid model predictive controller is introduced. To this end, the underlying mixed-integer nonlinear programming (MINLP) problem is transformed into a relaxed mixed-integer quadratically constrained programming (MIQCP) problem, suitable to generate feasible robot trajectories online. The proposed algorithm is implemented and validated on an experimental setup using the robot operating system (ROS) software and a robot arm performing discrete pick-and-place tasks.